Conditional Unconstitutionality and Compelling Urgency: How Constitutional Court Rulings on The Job Creation Law Are Reshaping the Political Direction of Indonesian Labor Law - Ujang Charda (Lembaga Bale Literasi, 2026)
The enactment of Law Number 11 of 2020 concerning Job Creation through the omnibus law method triggered widespread controversy because it was considered a procedural defect and ignored public participation. The Constitutional Court through Decision Number 91/PUU-XVIII/2020 declared the law conditionally unconstitutional and ordered improvements within two years. Instead of carrying out this mandate, the government issued Perppu Number 2 of 2022 with the pretext of a compelling emergency, which was later passed into Law Number 6 of 2023. This study aims to analyze the impact of conditional unconstitutional rulings on legal certainty and examine the constitutionality of the coercive emergency mechanism and its implications for the political direction of Indonesian labor law. The methods used are normative legal research with a legislative approach, a case approach, and a conceptual approach. The results of the study show that conditional unconstitutional decisions create dualism in the applicability of norms that are contrary to the principle of legal certainty. The issuance of the Perppu does not meet the objective parameters of urgency that force and ignore the standard of meaningful participation, so it can be qualified as constitutional disobedience. Overall, this dynamic shifts labor law politics from a welfare state paradigm to an investment orientation, which threatens the constitutional protection of workers' rights